If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 111 = -6x + 153 Reorder the terms: 111 + 1x = -6x + 153 Reorder the terms: 111 + 1x = 153 + -6x Solving 111 + 1x = 153 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 111 + 1x + 6x = 153 + -6x + 6x Combine like terms: 1x + 6x = 7x 111 + 7x = 153 + -6x + 6x Combine like terms: -6x + 6x = 0 111 + 7x = 153 + 0 111 + 7x = 153 Add '-111' to each side of the equation. 111 + -111 + 7x = 153 + -111 Combine like terms: 111 + -111 = 0 0 + 7x = 153 + -111 7x = 153 + -111 Combine like terms: 153 + -111 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| .11xa+4=-21 | | 10x+2x+160=180 | | (0.5x-8)-(0.5(-0.5x-8))-2=x | | 2(x+4)=14+8 | | 4-7i/5 | | 4x+7y+2= | | 2n^2+84=26n | | 4x^2-5x=9 | | C=6.28(x-1) | | x^5=50 | | 5x+7=-41-3x | | .5x^2-x-4=0 | | x^5=0.09 | | C=6.29(x-1) | | -4x-9y=-25 | | 15=.85*x | | C+6=((21+c)+6)*5 | | 5/5=x | | x^2+93x+285=0 | | d^5=0.09 | | -5(-4+x)-2=x-2(x-8)-18 | | 20y=4x+24 | | 3x-5=8x+8 | | .12x+.095y=.111 | | 3t^2+5t+6= | | 12x+4=13x+6 | | 7-4(z-8)= | | 3y-13=20 | | 3(8y-4)=2(y-6) | | 1/3x3x12 | | t+1-4t=-20-1 | | -3(y+1)-(-2y-7)=4 |